Case Report: Mycoplasma pneumoniae–associated acute pancreatitis - Sun, Hong; Wang, Wei-Qun; Lin, Long; Shao, Zheng-Yang; Zhan, Lu; Tang, Lan-Fang (Frontiers in Pediatrics, 2024)
Mycoplasma pneumoniae is the primary pathogen causing community-acquired pneumonia in children, accounting for approximately 10% to 40%. It can lead to various extrapulmonary complications, including acute pancreatitis, which has been reported in about 30 cases till now. Here, we report a 4-year-old girl who presented with fever, cough, and elevated levels of Mycoplasma pneumoniae IgM antibodies, followed by the onset of abdominal pain, elevated lipase, and elevated blood and urine amylase. The abdominal CT implied diffuse inflammation of the pancreas.Serum inflammatory cytokines, such as IL-2, IL-6, IL-17A, TNF, and IFN-γ were elevated. After excluding other causes, it was determined that Mycoplasma pneumoniae infection was the cause of her acute pancreatitis. She was treated with macrolides and glucocorticoids and ultimately made a full recovery. Therefore, acute pancreatitis should be included in the differential diagnosis for patients with Mycoplasma pneumoniae infection who present with abdominal pain. Inflammatory cytokines may play a role in mediating pancreatic damage.